Equilibrium Economics and Business-Cycle Theory: A Commentary - Souter, R. W. (Quarterly Journal of Economics, 1930)
I. Dr. Kuznets' methodological scepticism, 40. — II. Lederer, Loewe, and Carrel on equilibrium economics; the empiricorealist as circular reasoner, 42. — III. The equilibrium concept and economic dynamics, 55. — IV. Rosenstein-Rodan "discovers" orthodox economic theory, 63. — V. Business cycles and the Laws of Chance, 67. — VI. The program of Empirico-Realism provides neither a synthesis nor a call to economic theorists to abandon their evil courses, 81. — VII. The real problem of economic dynamics, 86.